Hospital Safety Climate Assessment toward Attitude's Nurses Based on Sammer's Model Case study: An academic General and A specialized Hospital in Tehran (Iran) - Katayoun Jahangiri; Parisa Akbaridana; Hasti Borgheipour; Ghazaleh Monazami Tehrani (Iranian Journal of Health, Safety and Environment, 2020)
Safety climate has become an important issue in organizational safety management of health systems. The aim of this applied study was assessment safety climate in general and specialized academic hospitals based on Sammer's model, to introduce a model with the specific framework to assess climate safety in Iranian hospitals, moreover, to reduce medical errors and incidents, also to increase patient safety. This model consists of seven dimensions: leadership, teamwork, evidence-based practices, communication, learning, justice and patient-centeredness. So a descriptive -comparative study was undertaken through a methodology including 3 phases. Data were collected by a modified questionnaire based on the Hospital Survey on Patient Safety Culture (HSOPSC) from 217 nurses and an In-depth interview with 52 nurses in both hospitals. According to the results in the general hospital, leadership, patient-centeredness and learning was recognized as the most effective factors, however, in the specialized hospital, the most important factors were patient-centeredness and justice. Seven dimensions of Sammer's model are effective in safety climate assessment, but they are not enough to assess safety climate Iranian hospitals. Adding other factors such as safety and standardized hospital building space, the safety of equipment, physical factors in the workplace, Social and culture factors and terms and conditions governing the hospital settings can help to complete the model and provide an integrated and more consistent one to take an effective step in assessing overall hospital safety climate.